2024
DOI: 10.1101/2024.02.14.580266
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adaptive diversification through structural variation in barley

Murukarthick Jayakodi,
Qiongxian Lu,
Helene Pidon
et al.

Abstract: Pangenomes are collections of annotated genome sequences of multiple individuals of a species. The structural variants uncovered by these datasets are a major asset to genetic analysis in crop plants. Here, we report a pangenome of barley comprising long-read sequence assemblies of 76 wild and domesticated genomes and short-read sequence data of 1,315 genotypes. An expanded catalogue of sequence variation in the crop includes structurally complex loci that have become hot spots of gene copy number variation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 128 publications
0
1
0
Order By: Relevance
“…Although there are new reports of scald resistance, most recently on chromosomes 2H (Cope et al 2021), 5H (Coulter et al 2019;Zantinge et al 2019;Büttner et al 2020;Cope et al 2021) and 6H (Coulter et al 2019;Ijaz et al 2024), in some cases the resistance has been mapped to previously reported loci and it is unclear if the 'new' resistance is an allele of a currently known gene, or represents a closely linked gene. However, with the availability of an increasing number of genome assemblies (Jayakodi et al 2020(Jayakodi et al , 2024Mascher et al 2017Mascher et al , 2021 characterization of the various scald loci should be possible and allow a better understanding of the resistance located in these regions. To date, no single resistance locus has been cloned or functionally characterized, although several groups have targeted specific loci (Cope et al 2021 (5H); Coulter et al 2019 (Rrs18 on 6HS); Looseley et al 2020 (Rrs1Rh4 on 3HS); Marzin et al 2016 (Rrs2 on 7H); Wang et al 2020 (QSc.VR4 on 4H).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are new reports of scald resistance, most recently on chromosomes 2H (Cope et al 2021), 5H (Coulter et al 2019;Zantinge et al 2019;Büttner et al 2020;Cope et al 2021) and 6H (Coulter et al 2019;Ijaz et al 2024), in some cases the resistance has been mapped to previously reported loci and it is unclear if the 'new' resistance is an allele of a currently known gene, or represents a closely linked gene. However, with the availability of an increasing number of genome assemblies (Jayakodi et al 2020(Jayakodi et al , 2024Mascher et al 2017Mascher et al , 2021 characterization of the various scald loci should be possible and allow a better understanding of the resistance located in these regions. To date, no single resistance locus has been cloned or functionally characterized, although several groups have targeted specific loci (Cope et al 2021 (5H); Coulter et al 2019 (Rrs18 on 6HS); Looseley et al 2020 (Rrs1Rh4 on 3HS); Marzin et al 2016 (Rrs2 on 7H); Wang et al 2020 (QSc.VR4 on 4H).…”
Section: Introductionmentioning
confidence: 99%